Risk assessment of Haier Groupas overseas investment under International financial reporting standards - Zhong, Bin; Soh, Wei Ni; Ong, Tze San; Muhammad, Haslinah Bt.; He, Chun Xi (Frontiers Media S.A., 2022)
With the development of economic globalization and the policy guidance of International Financial Reporting Standards (IFRS), the overseas investment of Chinese enterprises has been greatly affected. To study the overseas investment risks of Chinese enterprises, this paper applies a risk analysis model to summarize and analyze the results of overseas investment of Haier from 2008 to 2020. This paper defines the risk analysis model as risk identification, risk assessment, and risk response, and studies overseas investment risks including political, economic, cultural, legal, cost, epidemic, and business risks. (1) The existence of various risks is identified in the company’s overseas investment projects; (2). The overseas investment risks of Haier are evaluated, through a comprehensive evaluation method combining qualitative and quantitative, financial data, and market response; (3). In view of the deficiencies of the existing risk prevention measures in the overseas investment of enterprises, some reasonable suggestions are purposed. The innovation of this paper are: This paper combines IFRS 9, IFRS 15, and IFRS 16, selects theories, and combines cases to evaluate the risks of overseas investment that are difficult to quantify, and analyzes the risks of overseas investment by Z-value models and market effects. This research method has pertinence and applicability to enterprises investing overseas.